Bacterial infection, immune responses, and autophagy in lutzomyia longipalpis sand flies - Heerman, Matthew C. (Kansas State University, 2016)
Microbial communities residing within the midgut of insect vectors play a critical role in the response to various zoonotic and human pathogens, and can directly alter the development and survival of the insects. Sand flies are the primary vector of Leishmania, the causative pathogen of leishmaniasis, a neglected tropical disease. Sand flies acquire many microbes from the soil where immature stages develop until emergence as adults. Gram-negative Pantoea agglomerans and gram-positive Bacillus subtilis are two bacteria commonly associated with sand fly populations. Here, I demonstrated that an EGFP- and a GFP-expressing version of these two bacteria localize to different compartments of the midgut; a phenomenon that is achieved, in part, to pH differences found across the length of the gut. Additionally, P. agglomerans is able to selectively induce midgut epithelial apoptosis while B. subtilis does not. This is accompanied by differential immune and homeostasis responses to both bacteria highlighted by immune pathway suppression via the Poor Immune Response upon Knock-in (Pirk) gene. These effects may actually be representative of a broader type of response to bacterial infection that might be present across several insect species. Finally, I demonstrated that during metamorphosis the sand fly relies, at least in part, upon the activation of multiple genes from the autophagy pathway to aid in generating adult tissues. More specifically, I demonstrate, using microscopy, the presence of ATG6 in the cytoplasm of developing midgut epithelial cells of the sand fly pupae.
Keywords: Immunity; Autophagy; Leishmania; Sand flies; Metamorphosis; Pantoea agglomerans